Postoperative management and surgical decision-making in scleroderma: insights from a case study - Hakim, Tahmina; Tong, Edward; Selvendran, Selwyn (International Surgery Journal, 2025)
Scleroderma, a chronic autoimmune disease characterized by diffuse fibrosis, poses significant challenges for wound healing and postoperative recovery. The fibrotic changes and altered collagen production associated with scleroderma can complicate surgical outcomes, including wound healing and adhesion formation. This case report highlights the unique challenges faced in the surgical management of scleroderma patients, focusing on the postoperative appearance of the stoma, the risk of inflammatory adhesions and the implications of laparoscopic surgery in these patients. A 55 years old female with diffuse scleroderma, complicated by contractures, acro-osteolysis and multiple other systemic issues, presented with abdominal pain and a perforated sigmoid colon caused by an ingested foreign body. She underwent a laparoscopic Hartmann’s procedure. Postoperatively, the stoma appeared necrotic on day 2, though it was functionally healthy. Subsequent complications included small bowel obstruction and adhesions, necessitating additional surgical interventions. Scleroderma affects wound healing due to fibrotic changes and impaired collagen deposition. In this case, the necrotic appearance of the stoma was likely due to inflammatory changes rather than true necrosis. Laparoscopic surgery, while beneficial in reducing tissue trauma and complications, still presents risks in scleroderma patients, including adhesion formation. Early-stage scleroderma patients may experience fewer fibrotic changes but are still at risk for postoperative complications. Scleroderma patients require careful management to mitigate surgical complications. Laparoscopic approaches can reduce trauma and recovery time but do not eliminate the risk of adhesions and other complications. Ongoing monitoring and tailored postoperative care are essential for optimizing outcomes in these patients.